2019
DOI: 10.1016/j.cell.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Membrane Transporter MmpL3, an Anti-TB Drug Target

Abstract: Graphical Abstract Highlights d The crystal structure of Mycobacterium smegmatis MmpL3 has been determined d Two Asp-Tyr pairs in the TM region of MmpL3 facilitate proton-translocation d SQ109, an anti-TB drug, binds inside the protontranslocation channel of MmpL3 d Rimonabant, an antagonist for the cannabinoid receptor CB 1 , also inhibits MmpL3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
373
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(392 citation statements)
references
References 87 publications
(86 reference statements)
14
373
0
1
Order By: Relevance
“…The assay used a M . tuberculosis cytochrome bd oxidase deletion mutant cydKO , which is hypersusceptible to compounds such as imidazopyridines that target the QcrB subunit of the qcrCAB‐encoded cytochrome bc1 complex . No MIC shift was observed when the cydKO mutant was tested against all selected N ‐acetylazaaurones (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The assay used a M . tuberculosis cytochrome bd oxidase deletion mutant cydKO , which is hypersusceptible to compounds such as imidazopyridines that target the QcrB subunit of the qcrCAB‐encoded cytochrome bc1 complex . No MIC shift was observed when the cydKO mutant was tested against all selected N ‐acetylazaaurones (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…From Sargocentron spiniferum (Forsskål) (Holocentridae) in the South China Sea (as Benedenia sargocentron ) (Zhang et al 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al (2001) described Benedenia sargocentron on Sargocentron spiniferum from the South China Sea. However, Deveney and Whittington (2010) determined that B. sargocentron was a junior synonym of B. hawaiiensis , and proposed keeping B. hawaiiensis as the valid name.…”
Section: Resultsmentioning
confidence: 99%
“…The superimposition of the M. abscessus MmpL3 model onto the M. smegmatis MmpL3 structure showed that the drug binding site formerly described was conserved in the transmembrane domain of the M. abscessus MmpL3 (gold sphere in Figure ). Interestingly, this cavity is in the vicinity of residues previously reported to participate to the proton relay . This binding pocket is composed of two hydrophobic cavities, designated Up‐ and Bottom‐pockets (U and B in Figure c) and comprises also a more polar cavity, designated Middle‐pocket (M in Figure c).…”
Section: Resultsmentioning
confidence: 95%
“…The RMSD calculated on the C α of the template is around 0.4 Å and 96 % of the residues are within the Ramachandran criteria. The superimposition of the M. abscessus MmpL3 model onto the M. smegmatis MmpL3 structure showed that the drug binding site formerly described [33] was conserved in the transmembrane domain of the M. abscessus MmpL3 (gold sphere in Figure 4). Interestingly, this cavity is in the vicinity of residues previously reported to participate to the proton relay.…”
Section: Molecular Modellingmentioning
confidence: 96%